Madanadi Gana With Special Reference To Madanadi Nighantu Or Chandra Nighantu - Rabb, Umakant N (International Research Journal of Ayurveda & Yoga, 2020)
Madanandi Gana is integral part of Madanadi Nighantu. The Madanadi Nighantu is also called as Chandra Nighantu. The author of this Chandra Nighantu is Chandra Nandana who was the one of the Kashmiri Pandit well versed in Ayurveda Shastra. He wrote Padartha Chadrika Tika on Asthanga Hridaya. This Madanadi Nighantu would be placed in 12 century. Because one of the Kashmiri Vidwan Kshira Swami in his Amarakosha Tika he mentioned Chandra. The Madanadi Gana comprises 23 drugs. Viz; Madana, Madhuyasthi, Katuka alabu/ Katu tumbi, Nimba, Maha nimba, Bimbi, Indravaruni, Vana Trapusa, Kutaja, Murva, Devadali, Vidanga, Vetasa, Chitraka, Danti, Dravanti, Koshataki, Karanja, Pippali,Pippalimoola, Saindhva Lavana, Sauvarchala Lavana, Vida Lavana, Samudra Lavana, Vacha, Sukshma Ela, Sthula Ela, Harenu, Sarshapa, Shweta Sarshapa. Among these Madana, Yasthimadhu, Torai, Nimba, Bimbi, Vishala, Trapusa, Kutaja, Murva, Devadali, Vidanga, Vidula, Chitraka, Chitra, Koshataki, Karanja, Pippali, Lavana, Vacha, Ela, Sarshapa all these drugs are Chardi Karaka or Vamana Karaka which induces vomiting. Here an attempt is made to highlight these drugs with their botanical name, family along with pharmacological activities are mentioned strictly on bases of the Madanadi Nighantu. Further scope of study is to evaluate these drugs having Roshogna Karma(Anti viral actions), Krimighna(Anti helminthic actions), Jwaraghna(Anti pyretic actions), Shoolahara(Analgesic and anti spasmodic actions) Garbhapatakara(Anti abortive actions), with modern parameters.